The ASAS-SN catalogue of variable stars III: variables in the southern TESS continuous viewing zone. Issue 1 (13th February 2019) - Jayasinghe, T; Stanek, K Z; Kochanek, C S; Shappee, B J; Holoien, T W-S; Thompson, Todd A; Prieto, J L; Dong, Subo; Pawlak, M; Pejcha, O; Shields, J V; Pojmanski, G; et al.
Abstract: The All-Sky Automated Survey for Supernovae (ASAS-SN) provides long-baseline (∼4 yr) light curves for sources brighter than V ≲ 17 mag across the whole sky. The Transiting Exoplanet Survey Satellite ( TESS ) has started to produce high-quality light curves with a baseline of at least 27 d, eventually for most of the sky. The combination of ASAS-SN and TESS light curves probes both long- and short-term variability in great detail, especially towards the TESS continuous viewing zones (CVZ) at the ecliptic poles. We have produced ∼1.3 million V -band light curves covering a total of ${\sim }1000 \, \rm deg^2$ towards the southern TESS CVZ and have systematically searched these sources for variability. We have identified ∼11 700 variables, including ∼7 000 new discoveries. The light curves and characteristics of the variables are all available through the ASAS-SN variable stars data base (https://asas-sn.osu.edu/variables ). We also introduce an online resource to obtain pre-computed ASAS-SN V -band light curves (https://asas-sn.osu.edu/photometry ) starting with the light curves of the ∼1.3 million sources studied in this work. This effort will be extended to provide ASAS-SN light curves for ∼50 million sources over the entire sky.